Produtos naturais: atualidade, desafios e perspectivas - Pinto, Angelo C.; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Lopes, Norberto Peporine; Epifanio, Rosângela de Almeida (Sociedade Brasileira de Química, 2002)
This article offers an overview on the historical facts and the recent state of art of Chemistry of Natural Products which, in the course of 25 years of SBQ, have led to the present development of this area in Brazil. In addition, this article deals with the last trends on Natural Products in Brazil and also in developed countries.
Current status, challenges and trends on natural products in Brazil
Keywords: Chemistry of Natural Products; 25 years of SBQ; historical facts and trends